The Composition of Trade within Import-restricted Product Categories - Falvey, Rodney E. (Journal of Political Economy, 1979)
Quantitative restrictions imposed on product categories have been observed to shift the composition of imports with these categories in favor of relatively more expensive items. This paper applies Alchian and Allen's proposition concerning the effects of transportation costs on the composition of demand to explain this phenomenon. It is also shown that the same effects occur under specific tariffs but do not pertain to ad valorem tariffs or value restrictions.